Krishna Mohan Banerjea : Christian apologist. - Philip, T. V. (Confessing the faith in India series ;, 1982)
On the life and work of Krishna Mohan Banerjea, 1813-1885, Indian Missionary, scholar, and patriot; with special reference to Bengal renaissance and Hindu converts.